THE GLOBAL FINANCIAL CRISIS AND ECONOMIC INTEGRATION: EVIDENCE ON ASEAN-5 COUNTRIES - Hakim, Lukman; Dahalan, Jauhari (Journal of Indonesian Economy and Business, 2009)
The ASEAN Charter has been ratified by the ten member countries of ASEAN in 2008.Â This is to reaffirm the commitment of the member countries to the establishment of theÂ ASEAN free trade area by 2015. The ASEAN members must prepare themselves with theÂ economic and non economics aspects to be ready facing this era. Nevertheless, the globalÂ financial crisis could be a major hindrance to the implementation of the ASEAN free tradearea. In this study, we attempt to determine how the global financial crisis could possiblyÂ affect the creation of the regional economic integration among ASEAN countries.The study based on Newtonian paradigm on economic regional or namely the gravityÂ model. Gravity model explored the economic relation of the many regions or countries.The core properties of gravity model are export, GDP, population and distance intersÂ countries. This followed by the analysis of the possibility of the economics integrationusing the core gravity model. Next, we will incorporate the Exchange Market PressureÂ (EMP) as the financial crisis index to the core gravity model, to determine the influence offinancial crisis in ASEAN-5âs economic integration. We will use the panel data method toÂ execute the model. The result indicates EMP giving negative effect on ASEAN-5âseconomic integration. In overall result reported here indicate that economic integration isÂ possible to implement on ASEAN-5 countries. But, the global financial crisis will be threatÂ implementation of the economic integration.Keywords: economic integration, gravity model, global financial crisis.